Financial interventions and movement restrictions for managing the movement of health workers between public and private organizations in low- and middle-income countries (Review) - Rutebemberwa, E.; Kinengyere, A. A.; Ssengooba, F.; Pariyo, G. W.; Kiwanuka, S. N. (Cochrane Database of Systematic Reviews, 2014)
on the proportion of the population served by public or private organizations in a particular setting, this movement may result in imbalances in the number of healthcare providers available relative to the population receiving care from that sector. However, both public and private organizations are needed as each sector has unique contributions to make to the eDective delivery of health services. Objectives To assess the eDects of financial incentives and movement restriction interventions to manage the movement of health workers between public and private organizations in low- and middle-income countries. Search methods We searched the Cochrane Central Register of Controlled Trials (CENTRAL) (10 November 2012);EMBASE(7June 2011); LILACS (9 June 2011); MEDLINE (10 November 2012); CINAHL (13 August 2012); and the British Nursing Index (13 August 2012).
Keywords: health workers; public or private organizations